Light emitting diode (led) chip fabrication using low temperature processes - Tahan, Muliana; Nayan, Nafarizal; Bakri, Anis Suhaili; Rizan, Elfa Rizon (Penerbit Uthm, 2019)
Commercial light emitting diode (LED) chips are fabricated using metal organic chemical vapor deposition (MOCVD) process, which require high temperature process of above 1000 degree Celsius (◦C). Therefore, alternative processes such as pulse sputtering deposition (PSD), thermal annealing and electron beam have been investigated. Although a series of investigations have been reported on fabrication of LED chips employing various type of deposition, to our knowledge, most of these investigations are still not excluded from the high temperature process as their secondary process. Hence, this chapter reveals the investigation of LED chip fabrication at low temperature (which is below 1000 ◦C) and its possibility and reliability to emit light at wavelength of 442 nm, 460 nm and 520 nm. At this point, the use of combination of various techniques such as thermal annealing, PSD and electron beam helps to avoid expensive and high temperature techniques such as MOCVD. Development of low-cost production and commercial fabrication tools for LED and optoelectronic devices is a promising subject for future research. In addition, basic LED and device structure are also explained and illustrated in this chapter.